Juridical Review of Electronic Signature Implementation of Duties of Notary Offices in Contracting in Agreements in The COVID-19 - Rahmito Azhari; Wahyu Ramadhani; Teuku Okta Randa (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2021)
The rapid development of information technology has influenced the legal profession, one of which is the notary profession. The influence on the notary profession can be seen with the concept of cybernotary. In addition, in electronic transactions, personal data from users of electronic signatures is very susceptible to misuse, so it requires legal protection for subscribers. This study aims to determine the legal status of using electronic signatures in the implementation of the position of notary in electronic transactions and legal protection for notaries and signature users. Based on the research, this has resulted in a notary deed that is affixed with an electronic signature not having the power of proof like a contact but an underhand deed. Until this research was conducted, there were no laws and regulations that provided an opportunity for the use of electronic signatures in contacts. In practice, notaries in Indonesia until the time this research was conducted have not exercised their authority in electronic transactions due to the absence of laws and regulations that regulate this matter more clearly so that it can result in notaries having no legal basis.